ANALISIS NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER AND GOODS INDUSTRY BURSA EFEK INDONESIA - Delyma Agusti Meitasari; Muhadjir Anwar (Universitas Islam Kadiri, 2021)
Abstract Firm value is a term used to indicate the company’s financial condition in order to determine its future sustainability. There ase several factors that can affect firm value, namely capital structure, company growth, and profitability. This study aims to determine the effect of capital structure (DER), company growth (Assets Growth), and profitability (ROE) on firm value (PBV). Also, this study will also analyze the capital structure (DER) and company growth (Assets Growth) on profitability (ROE) in Consumer and Goods Industry companies listed on the Indonesia Stock Exchange. The population in this study are the Consumer and Goods Industry companies listed on the IDX for the periode 2017 – 2019. The sample in this study was determined by purposive sampling, so 47 companies were obtained from 58 Consumer and Goods Industry companier listed on the IDX. The type of data used is secondary data from www.idx.co.id and related company websites. The data analysis method uses is the path analysis method using the SPSS program. Keywords: DER, Assets Growth, ROE, PBV